South China Sea Disputes: Challenges And Opportunities For Preserving Regional Stability: Sengketa Laut Cina Selatan: Tantangan dan Peluang dalam Mempertahankan Stabilitas Regional - Iwan Isnurwanto (Perspektif Hukum, 2025)
The South China Sea (SCS) is a crucible of overlapping sovereignty claims, strategic rivalry, and valuable maritime resources. This article examines the principal challenges that the SCS disputes pose to regional stability—great power rivalry, ASEAN fragmentation, militarization and gray-zone coercion, and limitations of international law enforcement—and explores opportunities to mitigate tensions through diplomacy, legal instruments, confidence-building measures, and regional capacity-building. The study uses recent empirical evidence on trade flows, energy and fisheries significance, maritime incidents, and legal outcomes (notably the 2016 arbitral award) to assess the prospects for stability. The analysis argues that while legal rulings and multilateral norms provide an essential normative framework, political commitment, robust ASEAN coordination, and pragmatic, enforceable mechanisms (including an effective Code of Conduct) are necessary to transform the South China Sea from a chronic flashpoint into an arena of managed cooperation.